2023
DOI: 10.1101/2023.05.23.541921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of hippocampal mossy fiber-CA3 synapse function by a Bcl11b/C1ql2/Nrxn3(25b+) pathway

Abstract: The transcription factor Bcl11b has been linked to neurodevelopmental and neuropsychiatric disorders associated with synaptic dysfunction. Bcl11b is highly expressed in dentate gyrus granule neurons and is required for the structural and functional integrity of mossy fiber-CA3 synapses. The underlying molecular mechanisms, however, remained unclear. We show that the synaptic organizer molecule C1ql2 is a direct functional target of Bcl11b that regulates synaptic vesicle recruitment and long-term potentiation a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…In line with this, a recent study identified the synaptic organizer molecule C1ql2 as a direct functional target of Bcl11b at the mossy fiber synapses [89]. Interestingly, C1ql2 regulates synaptic vesicle recruitment to the active zone through direct interaction with Nrxn3(25b+), a specific splice variant of neurexin-3 that was linked to NDDs before [89,90]. Changes in synaptic signal transduction, including establishment, transport, and release of synaptic vesicles, as well as alterations on the postsynaptic side are known to be hallmarks of NDDs [91][92][93].…”
Section: Functions Of Bcl11b In Cns Developmentmentioning
confidence: 56%
See 2 more Smart Citations
“…In line with this, a recent study identified the synaptic organizer molecule C1ql2 as a direct functional target of Bcl11b at the mossy fiber synapses [89]. Interestingly, C1ql2 regulates synaptic vesicle recruitment to the active zone through direct interaction with Nrxn3(25b+), a specific splice variant of neurexin-3 that was linked to NDDs before [89,90]. Changes in synaptic signal transduction, including establishment, transport, and release of synaptic vesicles, as well as alterations on the postsynaptic side are known to be hallmarks of NDDs [91][92][93].…”
Section: Functions Of Bcl11b In Cns Developmentmentioning
confidence: 56%
“…In addition, the ultrastructural complexity of the synapses is lost, and the synaptic vesicles are disorganized upon the loss of Bcl11b [88]. In line with this, a recent study identified the synaptic organizer molecule C1ql2 as a direct functional target of Bcl11b at the mossy fiber synapses [89]. Interestingly, C1ql2 regulates synaptic vesicle recruitment to the active zone through direct interaction with Nrxn3(25b+), a specific splice variant of neurexin-3 that was linked to NDDs before [89,90].…”
Section: Functions Of Bcl11b In Cns Developmentmentioning
confidence: 81%
See 1 more Smart Citation